Prospective Elementary Science Teachers' GDO Awareness - Hasan Akgul; Hatice Mertoglu; Özlem Afacan (Sakarya University, 2013)
This is a research study designed to describe the Turkish prospective elementary science teachers' understandings about genetically differentiated organisms (GDO) as part of their perceptions about biotechnology. Therefore, it is a description of a current situation with a large sample. It is a quantitative survey in which individuals' understandings of GDO and the effects that were investigated. Research participants were 246 prospective elementary science teachers from three large-scaled universities located in three different cities in Turkey. Namely, Sakarya University in Sakarya, Marmara University in Istanbul and Ahi Evran University in Kırsehir. The "GDO Awareness Scale" was used as a data collection tool. It was developed by the researchers who were science educator, biology teacher and agricultural engineer. The original scale consisted of twenty- nine likert type items which were chosen from the item list generated by a team of specialists. Item analysis of the scale required to leave eleven of the items. Therefore data collected with the remaining eighteen item scale. Data display that research participants do not have adequate understanding and knowledge about the issues stated concerning most of the items.